2019
DOI: 10.2116/analsci.18p512
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Colorimetric Measurements of Antioxidant Capacity by Flow Injection Analysis with Paired Emitter Detector Diode

Abstract: An effective flow injection analysis (FIA) system employing paired emitter detector diode (PEDD) for simultaneous dual antioxidant assays is proposed. The total antioxidant capacity (TAC) was measured using the 2,2′-azino-bis(3ethylbenzothiazoline-6-sulfonic acid) (ABTS) assay in parallel with the ferric reducing antioxidant power (FRAP) assay. Ascorbic acid was used as the reference antioxidant and the TAC value reported as ascorbic acid equivalent (AAE). A 10port valve furnished with two injection loops allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…L-ascorbic acid solution (prepared using L-ascorbic acid reagent and 80% ethanol) was used as a standard curve, as per the methods of Sdiri et al [ 20 ] and Manthong et al [ 21 ]. The antioxidant capacity was expressed as ascorbic acid equivalent.…”
Section: Methodsmentioning
confidence: 99%
“…L-ascorbic acid solution (prepared using L-ascorbic acid reagent and 80% ethanol) was used as a standard curve, as per the methods of Sdiri et al [ 20 ] and Manthong et al [ 21 ]. The antioxidant capacity was expressed as ascorbic acid equivalent.…”
Section: Methodsmentioning
confidence: 99%
“…14 It presents advantages of low cost, easy operation and less time for analysis compared to chromatography. In addition, Manthong et al 15 proposed a FIA system using PEDD for the determination of antioxidant ins commercial fruit juice and instant tea products. Thongsaw et al 16 reported on the use of SPE-FI-CVAAS for mercury detection, and applied it to freshwater fish samples.…”
Section: Application Of Flow-based System For Quality Control and Foo...mentioning
confidence: 99%
“…19,20 Flow injection analysis (FIA) methods have the advantages of higher reproducibility, higher sample throughput, lower reagent consumption, and easier procedures than the batchwise methods. [31][32][33][34][35][36] Several FIA systems based on optode detectors have been reported. [21][22][23][24][25][26][27][28] Therefore, the combination of an FIA system and the optode detector based on L-RB is considered to be a very effective analytical method for determining AS.…”
Section: Introductionmentioning
confidence: 99%